The Impact of Recent Banking Regulations on the Market for Corporate Control - Henry N. Butler; J. Brady Dugan (Washington University Law Quarterly, 1990)
Part II of this Article briefly discusses the historical development of the regulation of bank capital, focusing on the 1989 risk-based capital adequacy regulations as well as the 1989 highly leveraged transaction guidelines and their impact on the banking industry's involvement in takeover transactions. This section also shows how the perverse incentives created by the present system of federal deposit insurance impact on the takeover market. Part III discusses the role of thrifts in corporate takeovers and the effect of the Financial Institutions Reform, Recovery and Enforcement Act of 1989, including its prohibition on thrifts' purchasing junk bonds. The concluding section speculates as to why these seemingly unwise regulations were adopted.
Keywords: Banking industry; Consolidation & amp; merger of corporations